Implementasi Metode Design Thinking Dalam Merancang E-Office Sebagai Pendukung Otomatisasi Perkantoran Desa - Tri Rahayu; Anita Muliawati; Rio Wirawan; Tjahjanto; Bambang Triwahyono; Widya Cholil (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2026)
Public services at Pabean Udik Village, Indramayu, are often hindered by paper-based bureaucracy, physical archive damage risks in coastal areas, and validation limitations due to the Village Head's external duties. This study aims to design an automated e-office application using the human-centered Design Thinking method. Through the Empathize, Define, Ideate, Prototype, and Test stages, initial Crazy 8 sketches were developed into high-fidelity interactive prototypes using Figma. The design encompasses public service interfaces (instant NIK integration, real-time document tracking) and internal staff management (digital attendance, leave management). System evaluation utilized Black-Box Testing and Usability Testing via the System Usability Scale (SUS) questionnaire involving 8 village officials. Functional tests achieved 100% success, while average SUS scores surged significantly from 61.5 (Marginal Low) in the first cycle to 79.5 (Acceptable/Grade B) in the second cycle following interface refinements. The application successfully reduced service time from 25–40 minutes to just 3–5 minutes.